2016
DOI: 10.1002/path.4707
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of TWEAK with Fn14 leads to the progression of fibrotic liver disease by directly modulating hepatic stellate cell proliferation

Abstract: Tumour necrosis factor‐like weak inducer of apoptosis (TWEAK) and its receptor fibroblast growth factor‐inducible 14 (Fn14) have been associated with liver regeneration in vivo. To further investigate the role of this pathway we examined their expression in human fibrotic liver disease and the effect of pathway deficiency in a murine model of liver fibrosis. The expression of Fn14 and TWEAK in normal and diseased human and mouse liver tissue and primary human hepatic stellate cells (HSCs) were investigated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 31 publications
(56 reference statements)
3
42
2
Order By: Relevance
“…S9). Of note, recent in vitro experiments with HSCs showed that Tweak could affect proliferation and not activation of HSCs36 while in our experiments HSC is not affected even though DEX decreased Tweak mRNA levels. Moreover, the DEX mediated inhibition of these signaling pathways apparently outperforms the potential downstream negative effects of an increased hepatocytic injury (higher ALT values) in the co-treated DEX/DDC animals (Figs 4 and 5).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…S9). Of note, recent in vitro experiments with HSCs showed that Tweak could affect proliferation and not activation of HSCs36 while in our experiments HSC is not affected even though DEX decreased Tweak mRNA levels. Moreover, the DEX mediated inhibition of these signaling pathways apparently outperforms the potential downstream negative effects of an increased hepatocytic injury (higher ALT values) in the co-treated DEX/DDC animals (Figs 4 and 5).…”
Section: Discussioncontrasting
confidence: 69%
“…Neither IFX, nor DEX, affected the proliferation of F4/80 + cells suggesting that the difference in the F4/80 + cells is mainly due to a difference in recruitment of macrophages. A possible mediator in the effect of DEX on these injury models is Tweak, a known mitogen for HSPCs that acts through the FN14 receptor35 and is necessary for liver fibrosis following chronic CCl 4 injury36. Tweak mRNA levels are decreased by DEX in both injury models, which could explain the lesser DR and fibrogenesis when DEX is used (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Decorin was another protein whose cardiac expression was modulated similarly in both ZO-C and ZL-C. Rapamycin increased this cardioprotective protein in both groups (Figure 6). Expression of profibrotic receptor for tumor necrosis factor-like weak inducer of apoptosis (TWEAK-R/Fn4) [46] was increased by over 2.4-fold by Rapamycin in the ZL-C heart. The T cell Ig and mucin domain-1 (Tim-1) protein is implicated in allograft rejection [47] and its expression also was increased by 2-fold by Rapamycin treatment.…”
Section: Resultsmentioning
confidence: 99%
“…TWEAK also leads to liver fibrosis progression by directly promoting HSC proliferation. TWEAK, and by enhancing SIRT1 expression and decreasing p53 acetylation, which assumedly inhibits HSC senescence [199, 200]. …”
Section: Mechanisms Of Hsc Activationmentioning
confidence: 99%